2015
DOI: 10.1007/s10620-015-3910-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Donor Age and Cold Ischemia on Liver Transplantation Outcomes According to the Severity of Recipient Status

Abstract: BackgroundProlonged cold ischemic time (CIT) and increased donor age are well-known factors negatively influencing outcomes after liver transplantation (LT).AimsThe aim of this study was to evaluate whether the magnitude of their negative effects is related to recipient model for end-stage liver disease (MELD) score.MethodsThis retrospective study was based on a cohort of 1402 LTs, divided into those performed in low-MELD (<10), moderate-MELD (10–20), and high-MELD (>20) recipients.ResultsWhile neither donor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…In a more complete clinical picture, prior risk analysis of CIT alongside other donor and patient variables reveals several interactions. Although the use of grafts from elderly donors does increase graft loss alone, it has been previously demonstrated that elderly grafts with prolonged cold ischemia have increased risk for graft loss at 5 years . It has also been shown that grafts with prolonged cold ischemia have lower graft survival when transplanted in moderate‐ and high‐MELD recipients but not when transplanted in low‐MELD recipients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more complete clinical picture, prior risk analysis of CIT alongside other donor and patient variables reveals several interactions. Although the use of grafts from elderly donors does increase graft loss alone, it has been previously demonstrated that elderly grafts with prolonged cold ischemia have increased risk for graft loss at 5 years . It has also been shown that grafts with prolonged cold ischemia have lower graft survival when transplanted in moderate‐ and high‐MELD recipients but not when transplanted in low‐MELD recipients .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of grafts from elderly donors does increase graft loss alone, it has been previously demonstrated that elderly grafts with prolonged cold ischemia have increased risk for graft loss at 5 years . It has also been shown that grafts with prolonged cold ischemia have lower graft survival when transplanted in moderate‐ and high‐MELD recipients but not when transplanted in low‐MELD recipients . Given the clear potential for confounding, our analysis controlled for numerous variables to isolate the effect of CIT.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with Feng and associates 5 that an ideal graft is homogeneous, allowing allocation of an optimal organ to anyone; however, nonideal grafts are heterogeneous, covering a wide spectrum of risk. In the latter case, allocating a suboptimal organ to a recipient with high MELD, 28,29 specific conditions, 30 or conditions with higher wait list mortality could interfere with the risk of patient survival against wait list mortality. 31 Therefore, an indicator should include this aspect in its design.…”
Section: Discussionmentioning
confidence: 99%
“…2,[12][13][14][15] Recurrence of hepatitis C is still common, persisting as the main problem of patients who are transplanted due to viral hepatitis, in need of effective treatment and, even, retransplant. 15 Among the fifteen patients who were notified with HCRI, only two were diagnosed with hepatitis C, presenting statistical significance in relation to the non-occurrence of HCRI, different from what has been found in an international study with univariate analysis, whose sample comprised 17 liver receptors with infection, and 34 without infection.…”
mentioning
confidence: 99%
“…In the international literature, transplanted patients presented a rate of 82.5%. 13 Research conducted at a single European center examined the survival of 313 liver receptors within two decades after the transplantation, pointing to infection as one of the most common causes of death after the surgical procedure. Of the patients analyzed, 141 died up to twenty years after the transplant, being 29 (20.6%) caused by various infections.…”
mentioning
confidence: 99%